Children at the Heart of Global Cardiac Surgery: An Advocacy Stakeholder Analysis. Issue 1 (January 2021) - Vervoort, Dominique; Zheleva, Bistra; Jenkins, Kathy J.; Dearani, Joseph A.
One in a hundred babies, or 1.3 million per year around the world, are born with congenital heart defects (CHD), of which over 70% will require medical or surgical treatment within their first year of life. In low- and middle-income countries, the majority does not receive the treatment they need or receive suboptimal care. Despite a higher pediatric cardiac surgical disease burden, low-income countries only have 0.07 pediatric cardiac surgeons per million pediatric population, compared to 9.51 per million in high-income countries. Here, we perform a stakeholder analysis of existing advocacy bodies within the field of pediatric global cardiac surgery and identify gaps and opportunities in advocating for cardiac care for children with CHD. We propose a framework to optimize civil society messaging in order to more effectively advocate domestically and internationally to hold national and international policy makers accountable for existing gaps and disparities in CHD care around the world.